2020
DOI: 10.1111/fare.12506
|View full text |Cite
|
Sign up to set email alerts
|

Parenting–Acculturation Match and Psychosocial Adjustment for Academically Gifted Chinese American Adolescents

Abstract: Objective Grounded in person–environment fit theory, we examine how different levels of parenting–acculturation match are associated with gifted Chinese American students' psychosocial adjustment. This study identifies parenting profiles indicated by psychological control and decisional autonomy granting and adolescents' acculturation profiles indicated by mainstream American culture and Chinese culture orientations. Background According to person–environment fit theory, optimal adjustment occurs when there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…The parents’ group believed that gifted and talented education should not occur only in the school context and all parent participants strongly believed education at home with the family was essential to nurture gifted children. This is consistent with previous research which shows that Chinese immigrant parents have reported discrepancies in education values and beliefs with schools (Chang et al, 2021). In order for parents to acknowledge the role teachers play in developing their children’s gifts and talents, it is essential for parents to be given the opportunity to hear the teachers’ voices about the strategies being utilized in the school/classroom context and discuss together the scope of a school/home partnership.…”
Section: A Culturally Responsive Frameworksupporting
confidence: 93%
See 2 more Smart Citations
“…The parents’ group believed that gifted and talented education should not occur only in the school context and all parent participants strongly believed education at home with the family was essential to nurture gifted children. This is consistent with previous research which shows that Chinese immigrant parents have reported discrepancies in education values and beliefs with schools (Chang et al, 2021). In order for parents to acknowledge the role teachers play in developing their children’s gifts and talents, it is essential for parents to be given the opportunity to hear the teachers’ voices about the strategies being utilized in the school/classroom context and discuss together the scope of a school/home partnership.…”
Section: A Culturally Responsive Frameworksupporting
confidence: 93%
“…In Australia, researchers have found that a significant reason for the academic performance of Chinese Australian being generally higher than Anglo-Australians is the extra support of their parents (Vialle, 2013). After investigating 222 academically gifted Chinese American adolescents' perceptions of parental involvement, Chang et al (2021) concluded that although these participants' levels of orientation toward American culture were higher than their levels of orientation toward Chinese culture, their views of their academic success and personal achievement were largely influenced by their parents. In Canada, researchers argued that another predictor of Chinese students' high achievement is that immigrant Chinese parents educate their children with more strict discipline and rules by setting aside homework time, limiting social time, and enrolling their children in private classes (Costigan et al, 2010).…”
Section: Confucian Philosophy Shapes Chinese Perceptions Of Gifted An...mentioning
confidence: 99%
See 1 more Smart Citation
“…This model showed the average relations between all the variables in Figure 1 across the groups. For all the dependent variables, we controlled for adolescents' age, gender (0 = male; 1 = female), lunch status (two dummy variables for free and reduced lunch, with full price as the reference group), generational status (two dummy variables for first and second-generations, with third-generation or beyond as the reference group), and family type (0 = single parent; 1 = two parent) because they were treated as covariates in previous research studying associations between family dynamics and adolescent outcomes in Chinese American and European American families (Chang et al, 2021). For each dependent/mediating variable, we also controlled for its previous level (i.e., the level at T1) because the previous levels of the dependent variables were associated with academic efficacy and/or academic performance at T1.…”
Section: Sem Analysismentioning
confidence: 99%
“…Cultural diversity research studies in the field of gifted and talented education in New Zealand have concentrated mainly on Māori and Pasifika students (Ministry of Education, 2013Education, , 2018. Other scholars have argued that teaching practices should be responsive to the cultural traits of all groups of gifted students (Bevan-Brown, 2011;Chang et al, 2021). However, few studies have examined Asian and/or Chinese descent gifted students in New Zealand.…”
Section: Introductionmentioning
confidence: 99%